EVALUASI STRUKTUR PIER HEAD YANG MENGALAMI PERUBAHAN BENTANG - Salsabilla, Nazya Tiara; Indianto, Andi; Yanuarini, Erlina (Politeknik Negeri Jakarta, 2025)
Cracking was observed on pier head P85-84 S of the JORR W1 Kebon Jeruk toll road, caused by an increase in span length and loading conditions that exceeded the original design specifications. This resulted in bending moments greater than those accounted for in the initial design, prompting the need for a structural capacity evaluation of the pier head. This study aims to assess whether pier head P85-84 S remains capable of withstanding the applied loads. The evaluation was conducted by analyzing the required reinforcement area, cross-sectional dimensions, and nominal moment capacity in comparison to the ultimate moment, using SAP2000 software. The analysis revealed that the pier head's capacity is inadequate. Under standard loading conditions, deficiencies of 1D19 and 5D19 were found in the bottom support and mid-span reinforcement, respectively. Under actual loading conditions, the reinforcement deficiencies increased to 2D19 at the bottom support and 8D19 at mid-span. Additionally, the comparison between the nominal and ultimate moment showed that the ultimate moment caused by the applied loads reached 71.12 ton·m, while the nominal moment was only 44.01 ton·m. These findings indicate that the current structure is insufficient to resist the existing loads. Therefore, structural strengthening is required, which may include the use of Fiber Reinforced Polymer (FRP), steel plate bonding, or external prestressing.